2010
DOI: 10.1111/j.1601-183x.2010.00607.x
|View full text |Cite
|
Sign up to set email alerts
|

Knockdown of FoxP2 alters spine density in Area X of the zebra finch

Abstract: Mutations in the gene encoding the transcription factor FoxP2 impair human speech and language. We have previously shown that deficits in vocal learning occur in zebra finches after reduction of FoxP2 in Area X, a striatal nucleus involved in song acquisition. We recently showed that FoxP2 is expressed in newly generated spiny neurons (SN) in adult Area X as well as in the ventricular zone (VZ) from which the SN originates. Moreover, their recruitment to Area X increases transiently during the song learning ph… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
81
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 88 publications
(83 citation statements)
references
References 50 publications
2
81
0
Order By: Relevance
“…It was then established that this gene is highly conserved from reptiles to humans, but especially among mammals, with strong evidence for recent selection in the human lineage (Enard et al, 2002;Scharff and Haesler, 2005). Due to current technological limitations, RNAi-mediated knockdown using a lentivral vector has been used to study the effect of reduced Foxp2 expression in Area X of the zebra finch brain, rather than a transgenic approach Schulz et al, 2010). In mice, heterozygous and homozygous Foxp2 knockouts as well as humanized knockins have been studied, and a mouse model has been developed with a conditional null (floxed) allele, allowing crosses to transgenic lines expressing Cre drivers for tissue-and timespecific conditional knockouts (French et al, 2007).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It was then established that this gene is highly conserved from reptiles to humans, but especially among mammals, with strong evidence for recent selection in the human lineage (Enard et al, 2002;Scharff and Haesler, 2005). Due to current technological limitations, RNAi-mediated knockdown using a lentivral vector has been used to study the effect of reduced Foxp2 expression in Area X of the zebra finch brain, rather than a transgenic approach Schulz et al, 2010). In mice, heterozygous and homozygous Foxp2 knockouts as well as humanized knockins have been studied, and a mouse model has been developed with a conditional null (floxed) allele, allowing crosses to transgenic lines expressing Cre drivers for tissue-and timespecific conditional knockouts (French et al, 2007).…”
Section: Discussionmentioning
confidence: 99%
“…In mice, heterozygous and homozygous Foxp2 knockouts as well as humanized knockins have been studied, and a mouse model has been developed with a conditional null (floxed) allele, allowing crosses to transgenic lines expressing Cre drivers for tissue-and timespecific conditional knockouts (French et al, 2007). Knockdown (in finches) or haploinsufficiency (in mice) of Foxp2 leads to altered or inaccurate vocalizations (Shu et al, 2005;, and in the finch this is associated with the altered density of spiny neurons in Area X (Schulz et al, 2010). Interestingly, the human version of Foxp2 has strong effects on the plasticity of the striaum and accelerates learning when introduced into mice (Schreiweis et al, 2014).…”
Section: Discussionmentioning
confidence: 99%
“…In juvenile birds, FoxP2 levels are increased in Area X, a striatal nucleus involved in vocal learning, during the critical period for song-learning (Haesler et al 2004) and are downregulated when adult males are practising their songs without directing them to a female (Miller et al 2008;Teramitsu and White 2006;Teramitsu et al 2010). Furthermore, viral-based knockdown of FoxP2 in Area X results in reduced spine density of medium spiny neurons (Schulz et al 2010) and impairs song-learning (Haesler et al 2007;Murugan et al 2013). Thus, both investigations of vocal learning in songbirds and of motor-skill learning in mouse models point to roles for FOXP2 in neural plasticity.…”
Section: Epilepsy-aphasia Spectrum Disordersmentioning
confidence: 99%
“…In a landmark paper, Haesler and colleagues (2007) reported that such FoxP2 knockdown in Area X (but not surrounding areas) during the developmental period of song acquisition led to incomplete and inaccurate imitation of tutor song. Further studies of knockdown birds indicate that FoxP2 loss yields reduced density for dendritic spines of spiny neurons (Schulz, Haesler, Scharff, & Rochefort, 2010) and interferes with dopamine modulation of activity propagation in a corticostriatal pathway involved in song variability (Murugan, Harward, Scharff, & Mooney, 2013). As with the mouse models, neural plasticity in striatal circuitry emerges as a common theme associated with this gene (Murugan et al, 2013;Schulz et al, 2010).…”
Section: Insights From Animal Modelsmentioning
confidence: 99%
“…Further studies of knockdown birds indicate that FoxP2 loss yields reduced density for dendritic spines of spiny neurons (Schulz, Haesler, Scharff, & Rochefort, 2010) and interferes with dopamine modulation of activity propagation in a corticostriatal pathway involved in song variability (Murugan, Harward, Scharff, & Mooney, 2013). As with the mouse models, neural plasticity in striatal circuitry emerges as a common theme associated with this gene (Murugan et al, 2013;Schulz et al, 2010). There is insufficient space available in this chapter to give a full account of all the relevant songbird studies; for further information on this burgeoning area of work, the interested reader is referred to reviews by Bolhuis et al (2010), Petri (2011), andWohlgemuth et al (2014).…”
Section: Insights From Animal Modelsmentioning
confidence: 99%